Andarilhos da esperança: estudo sobre a luta política impulsionada pela vida na rua e seus processos educativos sistematizada na experiência do Fórum da População de Rua de São Carlos/SP entre 2016 e 2017 - Almeida, Sara Ferreira de (Universidade Federal de São Carlos, 2018)
The more than 100 thousand people living on the streets in Brazil, without fundamental rights access is the result of a life organization system whose primary elements are: profit and private property; individualism and social segregation. Reactions of the Homeless in face of this reality led to the institution of public policy focused on the group in 2009. Academic production, especially in the field of Education, did not focus on the conquest of these rights, trying to understand if the processes of organization of the group in the struggle their problem or in their maintenance. This study sought to address this gap by explore emerging educational processes in such practice. The methodological course was built in two moments. The first one followed the presuppositions of the Philosophy of Liberation of Enrique Dussel that contributed the narrative of three militants of the Forum of the Homeless and of the Homeless National Movement in Campinas. They shared their own experiences from childhood to adulthood and from that to political engagement, making it possible to understand that life on the street dehumanizes and creates the substratum to humanize, but does not necessarily achieve that purpose. The political struggle unfolds in the practical field in distinct ways classified as: political practice for, with and of the Homeless. Each of them forms their subjects and they can be representatives and supporters of the street. These categories are organized by the conception of politics and education of Enrique Dussel and Paulo Freire. Such authors argue that when the voice of victimized subjects is heard in the construction of political struggle, it becomes an instrument of destabilization of what is given. It was this premise that guided the second moment of the sustained methodological course on the Systematization of Experiences, a research procedure that seeks to overcome the totalization of hegemonic science that hides popular knowledge. Adopting this strategy and anchoring it in the thinking of Oscar Jara Holliday and Marco Raul Mejía allowed the analysis of the political action of the São Carlos Homeless Forum from february 2016 to january 2017. Field notes, personal memories, minutes of the monthly meetings, photographic images, interviews and talk wheels were sources of recording and data collection. The conclusion of the investigation provided the defense that in the practice of political struggle carried out by those who have a street trajectory and their supporters, a narrative and knowledge capable of forming a proper reference point of this experience, which is always diverse and collective, is produced. The identification of the processes of his institution allowed to point out contributions to the political-educational activities of this popular group, besides giving clues to the construction of a scientific praxis that comes from the domain of the totalization of academic knowledge about the popular.

La existencia de más de 100 mil personas viviendo en la calle en Brasil es el resultado de un sistema de organización de la vida cuyos elementos fundantes son: el lucro y la propiedad privada; el individualismo y la segregación social. Las reacciones de la Población de Calle frente a esa realidad llevaron a la institución de la política pública dirigida al grupo en 2009. La producción académica, especialmente en el campo de la Educación, no se centró en la conquista de esos derechos buscando entender si los procesos de organización del grupo en la lucha política vislumbran la superación de su cuestión o en su mantenimiento. Este estudio buscó enfrentar esa laguna con el dibujo de los procesos educativos emergentes en tal práctica. El recorrido metodológico fue construido en dos momentos. El primero siguió los presupuestos de la Filosofía de la Liberación dusseliana que aportó la narrativa de tres militantes del Foro de la Población en Situación de Calle y del Movimiento Nacional de la Población de Calle en Campinas (Departamiento de San Pablo). Él y ellas compartieron sus propias vivencias de la infancia a la vida adulta y, de esa, al compromiso político, posibilitando la comprensión de que la vida en la calle deshumaniza y crea el sustrato para humanizar, pero no alcanza ese propósito necesariamente. La lucha política se desdobla en el campo práctico de maneras distintas clasificadas como: práctica política para, con y de la Población de Calle. Cada una de ellas forma sus sujetos pudiendo ser ellos representantes y partidarios de la calle. Estas categorías están organizadas por la concepción de política y educación de Enrique Dussel y Paulo Freire. Tales autores defienden que cuando la voz de sujetos victimados es escuchada en la construcción de la lucha política, se convierte en instrumento de desestabilización de lo que está dado. Fue esa premisa que orientó el segundo momento del recorrido metodológico sostenido sobre la Sistematización de Experiencias, procedimiento de investigación que busca superar la totalización de la ciencia hegemónica que oculta el conocimiento popular. Adoptar esa estrategia y anclarla en el pensamiento de Oscar Jara Holliday y Marco Raul Mejía permitió el análisis de la actuación política del Foro de la Población de Calle de São Carlos en el período de febrero de 2016 a enero de 2017. Notas de campo, memorias personales, actas de los encuentros mensuales, imágenes fotográficas, entrevistas y ruedas de conversación fueron fuentes de registro y recolección de los datos. La conclusión de la investigación proporcionó la defensa de que en la práctica de lucha política protagonizada por quienes tienen trayectoria de calle y sus partidarios se produce una narrativa y conocimientos capaces de realizar un referencial propio de esa experiencia, siempre diversa y colectiva. La identificación de los procesos de su institución permitió apuntar contribuciones al quehacer político-educativo de ese grupo popular, además de dar pistas a la construcción de una praxis científica que se desprende del dominio de la totalización del saber académico sobre lo popular.
Caminantes de la esperanza estudio sobre la lucha política impulsada por la vida en la calle y sus procesos educativos sistematizada en la experiencia del Foro de la Población de Calle de São Carlos / SP entre 2016 y 2017
Keywords: Processos educativos; Educação popular; População de rua; Luta política; Filosofia da libertação; Sistematização de experiência; Procesos educativos; Lucha política; Población de Calle; Filosofía de la liberación; Educación popular; Sistematización de experiencias; Educational processes; Political struggle; Homeless; Philosophy of liberation; Popular education; Systematization of experiences; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO